How to Approach Below-the-Ankle Arterial Interventions - Arslan, Bulent; Madassery, Sreekumar (Seminars in Interventional Radiology, 2023)
Critical limb ischemia, also referred to as chronic limb-threatening ischemia, is a major medical problem leading to limb amputations if not managed properly with a multispecialty team. Establishment of sufficient arterial flow to the foot is an integral part of this care. During the past two to three decades, arterial revascularization has become primarily endovascular with open surgical approaches significantly diminished in comparison. As techniques, tools, and experiences of the interventionalist have improved, the ability to recanalize more complex lesions has become more commonplace. We are at an age that even the arteries below the ankle can be accessed for complex interventions and even be recanalized if necessary. This article will discuss common arterial interventions performed below the ankle.
Keywords: pedal vasculature; angioplasty; recanalization; arterial; below the ankle; interventional radiology; peripheral arterial disease